2013
DOI: 10.1088/0022-3727/47/3/034002
|View full text |Cite
|
Sign up to set email alerts
|

Laser molecular beam epitaxy of ZnO thin films and heterostructures

Abstract: Abstract. We report on the growth of epitaxial ZnO thin films and ZnO based heterostructures on sapphire substrates by laser molecular beam epitaxy (MBE). We first discuss some recent developments in laser-MBE such as flexible ultraviolet laser beam optics, infrared laser heating systems or the use of atomic oxygen and nitrogen sources, and describe the technical realization of our advanced laser-MBE system. Then we describe the optimization of the deposition parameters for ZnO films such as laser fluence and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 96 publications
1
38
0
2
Order By: Relevance
“…In the following, we first highlight the recent progress of ZnO thin film technology and device fabrication (). Then, we will review our activities in the fields of injection, transport, and detection of spin‐polarized ensembles of charge carriers in ZnO using an all‐optical , an all‐electrical (), or a combined electrical/optical injection/detection scheme.…”
Section: Spin Transport In Znomentioning
confidence: 99%
See 1 more Smart Citation
“…In the following, we first highlight the recent progress of ZnO thin film technology and device fabrication (). Then, we will review our activities in the fields of injection, transport, and detection of spin‐polarized ensembles of charge carriers in ZnO using an all‐optical , an all‐electrical (), or a combined electrical/optical injection/detection scheme.…”
Section: Spin Transport In Znomentioning
confidence: 99%
“…Within the last decade there has been enormous progress in the growth of epitaxial ZnO thin films on Al 2 O 3 substrates by laser‐MBE and other techniques, in spite of the large lattice mismatch of 18.2%. In the following, we only give a brief overview on the growth issues, details have been published recently ().…”
Section: Spin Transport In Znomentioning
confidence: 99%
“…An essential surface modification needs to be done for each of the desired applications because surface effects radically influence the functionality of semiconductor nanocrystals. For preparing ZnO QDs on SiO 2 thin films a variety of methods have been employed such as pulsed laser deposition (PLD), sol-gel, sputtering, and molecular beam epitaxy (MBE) [9][10][11]. The sputtering technique is the most widely used among the above methods, because of its various advantages, such as a low deposition temperature, preferred orientation and high deposition rate on an amorphous substrate and large deposition area.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it is found that there exists several techniques, such as molecular beam epitaxy (MBE) [12], metalorganic chemical vapor deposition (MOCVD) [13], atomic layer deposition (ALD) [14], pulsed laser deposition (PLD) [15] and sputtering [16] techniques to be used for growing ZnO thin films. Though, MBE and ALD provides extrimely high precision over the grown layer thickness and its doping profile, their very low growth rate and low throughput restricts their use in batch to batch device fabrication.…”
Section: Introductionmentioning
confidence: 99%